Salbutamol delivery during non-invasive mechanical ventilation in patients with chronic obstructive pulmonary disease: a randomized, controlled study - KARAKURT, SAİT (SPRINGER, 2001)
Objective: We investigated the clinical response to equivalent doses of salbutamol delivered, via metered dose inhaler (MDI) during non-invasive mechanical ventilation (NIMV-MDI), during spontaneous breathing using a spacer (MDI-Spacer), and also during intermittent positive pressure breathing (IPPB). Setting: A respiratory intensive care unit. Design: Prospective, randomized, and placebo-controlled study. Patients: Eighteen stable patients with chronic obstructive pulmonary disease mean FEV1 = 38.5 +/- 8.8 % predicted). Results: Overall salbutamol administration induced, compared to placebo, a significant improvement in FEV1, irrespective of the mode of administration (+7.9 +/- 7.1 % or +108 +/- 91 ml for IPPB, +9.6 +/- 8.8 % or 112 +/- 67 ml for MDI-NIMV (inspiratory pressure = 14.3 +/- 1.8 cmH(2)O; expiratory pressure = none), and +10.8 +/- 11.4 % or 119 +/- 114 ml for MDI-Spacer, respectively). Delta FVC significantly increased from placebo only in MDI-NIMV (+214 +/- 182 ml P = 0.02). A second set of experiments performed in eight patients to ascertain the possible effect of NIMV on pulmonary function tests, showed a significant improvement from baseline values in FVC both after the delivering of placebo or salbutamol via NIMV-MDI (+206 +/- 147 ml and 208 +/- 145, respectively). FEV1 significantly increased only after salbutamol. No changes in gas exchange were observed after bronchodilator delivery. Conclusions: We show that delivery of bronchodilators via MDI with a spacer chamber during NIMV is feasible and induces a significant bronchodilator effect compared to placebo, even though it may be slightly less effective than the classical delivery system (MDI-Spacer).
Keywords: non-invasive ventilation; COPD; salbutamol; METERED-DOSE INHALER; COPD PATIENTS; BRONCHODILATOR DELIVERY; IPRATROPIUM BROMIDE; ACUTE EXACERBATIONS; ALBUTEROL; FENOTEROL; OXYGEN